Răspuns :
Răspuns
b) 63
Explicație pas cu pas:
[tex]a=36\\b=\frac{1}{6}a=\frac{36}{6}=6\\c=\frac{1}{2}(a+b)=\frac{42}{2}=21\\a+b+c=36+6+21=63[/tex]
a = 36
b = 1 pe 6
c = ( a + b ) : 2
-----------------
b = 36 : 6
( deoarece avem 1 , iar numitorul se împarte iar numărătorul se înmulțește)
b = 6
c = ( 36 + 6 ) : 2
c = 42 : 2
c = 21
a = 36
b = 6
c = 21
36 + 6 + 21 = 63
Succes !
b = 1 pe 6
c = ( a + b ) : 2
-----------------
b = 36 : 6
( deoarece avem 1 , iar numitorul se împarte iar numărătorul se înmulțește)
b = 6
c = ( 36 + 6 ) : 2
c = 42 : 2
c = 21
a = 36
b = 6
c = 21
36 + 6 + 21 = 63
Succes !